Políticas públicas de cultura para a dança no estado do Paraná - Silva, Silvana dos Santos (2017)
The artistic-cultural field of Parana is in process of (re) structuring, especially, after the approval of the National Plan of Culture. In this context, there is the subfield of dance, which according to IBGE survey in (2007), is constituted as one of the most practiced artistic languages by the population. Considering that only the elaboration of laws, programs and projects is not enough for the effectiveness of cultural actions for dance, due to the imbricated web of relations between the structure and the social agents. The research aimed to investigate the process of development of the Public Policies of Culture for dance in Parana, in interlocution with the political-bureaucratic and artistic-cultural fields, aiming the analysis of how the policies are structured and set off in the State. Therefore, it was necessary to study the public policies of culture in the scope of scientific-academic and legislative production, with a specific focus for the sub-field of dance in Parana; understand how the culture systems in the state are organized in the state in relation to the implications of this structuring in the development of dance projects; verify the cultural actions implemented and developed in the dance field through projects of cultural management bodies; and identify the cultural capital of public managers in relation to the artistic-cultural field and its demarcation in the management of dance in the investigated realities. As a theoretical-methodological reference, a sociological theory of Pierre Bourdieu was chosen, emphasizing the use of some of its concepts, such as: cultural capital, social capital, economic capital, symbolic capital, field and habitus, which have been shown as effective for this sociological analysis. A sample was composed by 19 public cultures managers, among them, the directors of the Cultural Foundation of Curitiba, the Secretary of State of Culture of Parana and 17 representatives of the largest regional cultural municipalities. In addition, two dance professionals linked to the Dance School and the Dance Corps of the Guaíra Theater Foundation were interviewed. The data collection instrument consisted of a structured interview with 43 questions, with the public managers of culture, besides specific questions directed to the dance professionals. Observed the differences between the counties in Parana, the results point to a dependence of public policies of culture for dance in relation to the dynamics that involve the interests of the agents in the pollical-bureaucratical field, (executive and legislative), of the organization of culture systems (management bodies, management tools, participation instances) and of the cultural capital of public managers (artistic and cultural field and dance subfield). In addition, other influences were evidenced in this process, namely: a) the volume of economic capital destined for culture and the social and symbolic capital of agents and cultural actions in dance; b) the action of the judiciary to regularize the hiring of dance professionals; c) dance institutions and professionals from the private sector and the third sector that are often the proponents and executors of the actions; d) the cultural need of the population for dance practices; e) and the specific cultural capital of dance professionals. This results in the understanding that public policies of culture for dance, in spite of their systemic organization, do not subsist in themselves, decoupled from the complex web of social relations, in which agents play an important role in its attainment.